Non-ischemic phenotypes of low-risk chest pain patients based on exercise stress echocardiography: a pilot study - Ryabova, Tamara; Abramenko, Elena; Yolgin, Ivan; Zavadovsky, Konstantin; Ryabov, Vyacheslav (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveA significant proportion (∼85%) of low-risk non-ST-elevation acute coronary syndrome (NSTE-ACS) patients do not receive objective confirmation of ischemia by stress echocardiography (SE), yet remain a healthcare burden due to lower long-term survival and overuse of medical services. We aimed to identify non-ischemic phenotypes in low-risk NSTE-ACS patients by analyzing a wide range of parameters available during exercise SE.MethodsInpatients [n = 103, median age 56 (46–65) years, 65 (63%) men] with suspected NSTE-ACS without high-risk criteria underwent exercise SE using a semi-supine cycle ergometer. Abnormal stress biomarkers [regional wall motion abnormalities (RWMAs), ST-segment depression, induced angina, peak systolic blood pressure, force-based contractile reserve (CR), heart rate reserve (HRR), and low exercise capacity] were used for phenotyping. Non-ischemic phenotypes were identified as patients not belonging to the clusters with the highest rates of RWMA, ST-segment depression, and induced angina. Invasive or non-invasive coronary angiography was used to assess coronary anatomy.ResultsThe majority (90%) of patients presented with one or more abnormal stress biomarkers. Cluster analysis revealed six phenotypes, four of which were classified as non-ischemic and identified in 65 (63%) patients. Non-ischemic phenotypes differed in the prevalence of hypertensive response, reduced CR, and reduced HRR. Among patients with non-ischemic phenotypes, the incidence of coronary artery disease was low (23%).ConclusionsFour non-ischemic phenotypes of low-risk NSTE-ACS patients were identified: “near-normal type,” “inotropic insufficiency type,” “hypertensive type,” and “chronotropic insufficiency type.” Further studies are needed to investigate the long-term significance of the obtained phenotypes.